ANALISIS KUALITAS PELAYANAN DI SMP PRINCE’S CRE@TIVE SCHOOL MENGGUNAKAN METODE IMPORTANCE-PERFORMANCE MATRIX - Rudy Vernando Silalahi; Samuel Kevin Sopar (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
Education is a crucial factor influencing a country's development. As scientific advancements accelerate, competition among educational institutions becomes more complex, necessitating innovative teaching and learning methods. To address the declining enrolment at Prince's Creative School, a thorough understanding of the expected service quality is essential for attracting more students. This research aims to identify the key service quality indicators at Prince's Cre@tive School and propose enhancements based on these indicators. Data was gathered through questionnaires distributed to 66 students to pinpoint significant issues needing attention. Additionally, in-depth interviews with school management were conducted to gain insights into the root causes of the problems and to gather improvement suggestions. Further analysis of the questionnaire data was performed using the IPA Matrix and Fishbone Diagram techniques. The analysis revealed five attributes that require performance enhancement, along with recommendations to improve these indicators. The principal emphasized the importance of addressing student needs (EE6), noting that while the mean importance was 3.52, the mean performance was 3.38. Other key areas included administrative staff assistance in providing necessary information (A2), with mean importance at 3.61 and mean performance at 3.41, as well as the comfort of the school hall (F2), which had a mean importance of 3.50 and mean performance of 3.36. Subsequent interviews with the principal sought to explore potential proposals for improvements, which were later reclassified.